The Effect of Compensation and Workload on Employee Ethical Behavior at PT. XYZ in Jakarta - Lutfi Akbar Fauzi; Didin Kristinawati (Politeknik Siber Cerdika Internasional, 2026)
Background: PT. XYZ is a national energy management and distribution company that applies Good Corporate Governance principles to ensure transparent and ethical operations. Despite improved employee compensation, the increasing number of ethical violation complaints over the past three years indicates ongoing challenges in maintaining employees' ethical behavior. Objective: This study examines the effects of compensation and workload on employees' ethical behavior at PT. XYZ using Equity Theory and the Job Demands–Resources Model to explain how compensation fairness and the balance between job demands and organizational resources influence ethical behavior. Methods: This study employs a quantitative method with a causal design, collecting data through Likert scale questionnaires distributed to 124 permanent employees of PT. XYZ. The variables analyzed include compensation and workload as independent variables, and employees' ethical behavior as the dependent variable. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the partial and simultaneous effects among the variables studied. Results: The SEM-PLS analysis revealed that compensation has a positive and significant effect on employee ethical behavior (path coefficient = 0.655; T-statistic = 15.173; p < 0.05), while workload has a negative and significant effect (path coefficient = -0.480; T-statistic = 10.414; p < 0.05). Simultaneously, both variables explain 79% of the variation in employee ethical behavior (R² = 0.790), demonstrating a strong predictive model (SRMR = 0.037). Conclusion: These findings confirm that fair compensation strengthens employee integrity, while excessive workload undermines ethical conduct. Organizations are advised to optimize compensation schemes and restructure workload distribution to cultivate a professional, ethical, and high-performance work environment.